Influência do Rompimento da Barragem do Valo Grande (Iguape, SP) nas Associações de Foraminíferos e Tecamebas. - EICHLER-COELHO, PATRÍCIA BECK; DULEBA, WÂNIA; EICHLER, BEATRIZ BECK; COELHO JR, CLEMENTE (Pesquisas em Geociências, 1996)
This paper deals with the probable consequences of the increase of water flow on the hydrographic and sedimentological parameters of the Cananéia-Iguape estuary and their relationship with the foraminifera and thecamoebians assemblages found before and after the Valo Grande dam's disruption. The sedimentological and biological parameters were obtained from each of the sixty samples of the collected bottom sediments. Before the dam’s disruption, the distribution of foraminifera and thecamoebians was apparently influenced by the substrate properties, such as grain size sorting and organic carbon content. After the dam's disruption, the bottom temperature was probably the responsible for the distribution of foraminifera and thecamoebians and for the total Textulariina and Ammonia tepida and Arenoparrella mexicana distribution patterns. Besides. very fine sand and bottom water salinity were probably the most influential factors in the distribution of Difflugia oblonga. Centropyxis aculeate and Centropyxis constricta.